Contribuição do budismo para a autoconstrução do ser humano na perspectiva de uma educação para a inteireza - Canever, Vanessa (2015)
This research aimed to investigate the Buddhist contribution to personal and professional lives of teachers, considering the self-construction of the Integral Human Being (Catanante, 2000). It had the following objectives: revisit the being a teacher and his teaching DO; identify aspects that Buddhism adds into personal and professional lives of teachers in their constitutive dimensions: social, emotional, spiritual and rational; analyze the possibilities of self-construction of human being, through the Buddhist teachings; interpret the benefits of Buddhist teachings over time for self-construction of the human being from the perspective of education for wholeness. The research is qualitative, a comprehensive-interpretative perspective (TURATO, 2003) and based on the understanding that changing the external occurs with self-knowledge and inner transformation (NÓVOA, 2009; PALMER, 2013). The research was conducted with two groups of subjects: the first, made up of four educators who have incorporated in their day to day, for more than five years, the teachings of Tibetan Buddhism, the Nyingma lineage; the second with six teachers, who are not practitioners of this philosophy. It was performed as data search strategies: weekly meetings to study and practice the Buddhist teachings (CHAGDUD, 2013); semi-structured interviews; and two instruments, called Wheel of Life - Being Integral and Form Being Integral, both created by this researcher, in order to support the subjects to careful reflection to the human being in its entirety. The weekly meetings were analyzed by Qualitative Analysis Basic (CRESWELL, 2010) and through steps presented by Severino (2000); semi-structured interviews were analyzed using the Text Analysis Discourse (MORAES & Galiazzi, 2011); and the instruments, the Analysis Descriptive Statistics (Appolinario, 2006). The investigation revealed that the contribution of Buddhism depends on the practice of the subjects, applying the teachings in daily life and the practice remains evident that Buddhism contributes to the self-construction of the human being from the perspective of education for wholeness, significantly. There was confirmation of how the Buddha are effective methods. The subjects who practiced Buddhism for two months experienced, in short, change in their perceptions, actions and consequently the results. With an observer stance of own thoughts, feelings and words, made them more responsible, loving actions and reaped therefore a more meaningful, peaceful and happy life. Buddhist teachers who have demonstrated a completely different life that they had before knowing Buddhism, more positive, compassionate, less suffering, after several years of practice. The results leave open spaces for further research, not only to expand knowledge, but in order to provide personal transformations and improvements in education and society, the self-construction of a whole human being from the perspective of education for wholeness.